2017
DOI: 10.2166/wst.2017.342
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of magnetic imprinted graphene oxide composite for catalytic degradation of Congo red under dark ambient conditions

Abstract: Magnetic imprinted N-doped P25/FeO-graphene oxide (MIGNT) was prepared with methyl orange as the dummy template and pyrrole as functional monomer for catalytic degradation of Congo red (CR). Hummers method and the hydrothermal method were used to synthesize FeO-GO and N-doped P25, respectively. The results of adsorption and degradation experiments showed that the adsorption capacity and catalytic degradation ability of the imprinted composite for CR were obviously higher than those of a non-imprinted one. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The results showed that the catalyst could rapidly degrade CR and is easily recycled. The degradation mechanism resembled that of the MIGNT catalyst [66].…”
Section: Hybridsmentioning
confidence: 65%
See 1 more Smart Citation
“…The results showed that the catalyst could rapidly degrade CR and is easily recycled. The degradation mechanism resembled that of the MIGNT catalyst [66].…”
Section: Hybridsmentioning
confidence: 65%
“…Magnetic materials have intrinsic advantages over non-magnetic ones as heterogeneous catalysts due to the facile magnetic separation of the catalysts from the reaction system after the catalytic process. For this purpose, Yang and co-workers [66] synthesized magnetic imprinted N-doped P25/F3O4-graphene oxide (MIGNT) and used it as a heterogeneous catalyst to degrade congo red (CR) under dark ambient conditions. The material had a high degradation efficiency for CR and could be recycled conveniently due to the magnetic properties of Fe3O4.…”
Section: Hybridsmentioning
confidence: 99%
“…13,14 The magnetic properties of iron oxide nanoparticles (MNP) are reported in several investigations, [15][16][17] resulting in a lower cost synthesis when compared to other metal oxides. 16,18,19 Decoration of the GO sheets with MNP had also been studied in order to obtain magnetic graphene oxide (MGO). [20][21][22] The GO characteristics such as low toxicity, thermal stability and hydrophilic property, when combined with magnetic properties from MNP on its surface, become a potential composite for relevant studies and new applications.…”
mentioning
confidence: 99%